Coexpression network analysis of proteins and metabolites time-course of two contrasting Eucalyptus grandis reponses to Austropuccinia psidii - Pinheiro, Ana Lúcia Mendes (2021)
The development of omics studies as genomics, transcriptomics, proteomics and metabolomics improved greatly our understanding of plant responses to different stresses, including biotic stress, providing insights on mechanisms that determine plant immune system success or pathogen invasion. However, molecular changes orchestrated by trees species in response to fungal infestation and how it is affecting disease outcome involving susceptibility or resistance responses, especially involving primary metabolism reconfigurations, remains poorly understood. Here, a 24h time-course of resistant and susceptible genotypes of Eucalyptus grandis were inoculated and mock-inoculated with Austropuccinia psidii, a biotrophic fungus responsible for rust disease in Eucalyptus, in order to characterize proteins and metabolites changes and divergences among the two selected genotypes. GC-MS based metabolomics and label-free proteomic analysis, were integrated using WGCNA package (Weighted Gene Co-Expression Analysis), to contrast resistant and susceptible responses in Eucalyptus grandis infected with Austropuccinia psidii. Integrated analysis revealed temporal divergences of protein-metabolites modules providing information of differences in photosynthesis and ROS generation, metabolism of lipids, spores germination, metabolism of amino acids, cell wall reinforcement, phytoalexins and defense responses. Our findings provide insights in key molecular mechanisms that underly the interactions between Eucalyptus grandis and Austropuccinia psidii and important features for enhancing molecular breeding efforts.